2001
DOI: 10.1177/152692480101100107
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Assessment of Living Organ Donors: Clinical and Ethical Considerations

Abstract: This article outlines psychosocial and ethical issues to be considered when evaluating potential living organ donors. Six types of living donors are described: genetically related, emotionally related, "Good Samaritan" (both directed and nondirected), vendors, and organ exchangers. The primary domains to be assessed in the psychosocial evaluation are informed consent, motivation for donating and the decision-making process, adequacy of support (financial and social), behavioral and psychological health, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 44 publications
0
51
0
Order By: Relevance
“…Despite federal regulations (36) and guidelines on the ethical evaluation of LD candidates (13,47,48), most transplant centers do not conduct a formal assessment of candidates' comprehension of the information provided during the consent process. This may be partly due to the lack of a reliable and valid assessment tool.…”
Section: Comprehension and Information Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite federal regulations (36) and guidelines on the ethical evaluation of LD candidates (13,47,48), most transplant centers do not conduct a formal assessment of candidates' comprehension of the information provided during the consent process. This may be partly due to the lack of a reliable and valid assessment tool.…”
Section: Comprehension and Information Needsmentioning
confidence: 99%
“…The Gordon transplant team should be mindful of this disparity particularly in the context of social and psychological pressures on women to donate to their spouses. Conversely, teams should also consider the risks to the family unit if donors are cleared to donate in terms of the need for healthy parents to raise children or financial hardships due to lost wages (15,48).…”
Section: Voluntarinessmentioning
confidence: 99%
“…However, requests from the general public to transplant centers for consideration of nondirected donation of a kidney or liver segment to anyone on the transplant wait list, may not be given full consideration. Although a few centers have piloted work with nondirected kidney donation, relevant concerns about motivation, judgment and risk appreciation on the part of donor candidates, as well as liability risks and ethics remain major issues (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Furthermore, transplant centers may lack the resources necessary for large-scale donor screening and education programs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been consistently found that kidneys from living donors lead to longer, healthier posttransplant lives (Olbrisch et al, 2001, Leo et al, 2003, Gill and Lowes, 2008. Figures show that 77% of kidneys from living donors will still be working 10 years after transplantation, whereas 72% of kidneys from deceased donors will still be functional at this point (NHS, 2015).…”
mentioning
confidence: 99%
“…Citations of note within the initially found papers were followed up, and it was found that existing qualitative literature on living kidney donation tends to focus on donors (see eg. Olbrisch et al, 2001, Lennerling et al, 2003, Brown et al, 2008, Challenor and Watts, 2013 or on dyads of recipients and donors Lowes, 2008, Gill andLowes, 2009) despite various researchers Lowes, 2008, de Groot et al, 2012) stating that living donor transplantation may be more psychologically complex for recipients than donors. One area in which there is more qualitative research on receiving organs is for adolescents, as detailed in Tong et al (2009)…”
mentioning
confidence: 99%